High-Resolution MRI Evaluation of Neonatal Brachial Plexus Palsy: A Promising Alternative to Traditional CT Myelography - Somashekar, D.; Yang, L.J.S.; Ibrahim, M.; Parmar, H.A. (American Journal of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: Despite recent improvements in perinatal care, the incidence of neonatal brachial plexus palsy remains relatively common. CT myelography is currently considered to be the optimal imaging technique for evaluating nerve root integrity. Recent improvements in MR imaging techniques have made it an attractive alternative to evaluate nerve root avulsions (preganglionic injuries). We aim to demonstrate utility of MR imaging in the evaluation of normal and avulsed spinal nerve roots. MATERIALS AND METHODS: All study patients with clinically diagnosed neonatal brachial plexus palsy underwent MR imaging by use of a high-resolution, heavily T2-weighted (driven equilibrium) sequence. MR imaging findings were reviewed for presence of nerve root avulsion from C5–T1 and for presence of pseudomeningocele. The intraoperative findings were reviewed and compared with the preoperative MR imaging findings. RESULTS: Thirteen patients (9 male, 4 female) underwent MR imaging; 6 patients underwent nerve reconstruction surgery, during which a total of 19 nerve roots were evaluated. Eight avulsions were noted at surgery and in the remainder, the nerve injury was more distal (rupture/postganglionic injury). Six of the 8 nerve root avulsions identified at surgery were at C5–6 level, whereas 1 nerve root avulsion was identified at C7 and C8 levels, respectively. The overall sensitivity and specificity of MR imaging for nerve root avulsions was 75% and 82%, respectively. CONCLUSIONS: Our preliminary results demonstrate that high-resolution MR imaging offers an excellent alternative to CT myelography for the evaluation of neonatal brachial plexus palsy with similar sensitivity compared with CT myelography. NBPPneonatal brachial plexus palsyCTMCT myelogram